map function using foldl or foldr in Haskell - haskell

I am writing a function my_map which takes a unary function and a list and returns the list resulting from mapping the function over all elements of the input list.
Main> my_map (^3) [1..5]
[1,8,27,64,125]
I tried it like this:
my_map :: (a -> b) -> [a] -> [b]
my_map f [] = []
my_map f (x:xs) = foldr (\x xs -> (f x):xs) [] xs
But after running above, I get only [8,27,64,125]. the first number 1 is not displaying in output.
Can anybody help me?

You are using the (x:xs) pattern in your arguments, but when you apply the fold, you only apply it to the xs part, which means your first element i.e. the one that x represents never gets processed. You need to change it to this:
my_map :: (a -> b) -> [a] -> [b]
my_map f xs = foldr (\y ys -> (f y):ys) [] xs
Since you are using foldr, you do not need to explicitly handle the empty list case. Moreoever, you do not need to specify the list in (x:xs) format.
Finally, my own preference is to avoid using the same name for function inputs and any helper functions or expressions in the function definition.That is why, I have used xs for the input list and y and ys for the parameters passed to the lambda.

"shree.pat18" is perfectly right, and also the comments are valuable. I learned a lot from that. Just make it better visible, and to explain the alternatives...
Answer
-- The problem is here ....................... vv
my_map f (x:xs) = foldr (\x xs -> (f x):xs) [] xs
-- --
The remaining part xs is aplied to foldr.
To fix just this, apply the whole list. This can be done by placing xx# before (x:xs). By that, the whole list is bound to xx.
-- vvv ........... see here ............... vv
my_map f xx#(x:xs) = foldr (\x xs -> (f x):xs) [] xx
-- --- --
Recommended impovement
Note: foldr can already deal with [] as input. Hence, my_map f [] = [] is not needed. But foldr would not be called when you apply [] to my_map. To get rid of my_map f [] = [], you need to remove the pattern matching, because (x:xs) matches only to lists with at least one element.
main :: IO ()
main = print $ my_map (^(3 :: Int)) ([1..5] :: [Integer])
my_map :: (a -> b) -> [a] -> [b]
my_map f xx = foldr (\x xs -> (f x):xs) [] xx
The answer is complete here. The rest below is for pleasure.
Further reductions
Simple expression instead of lambda expression
If you want to reduce the lambda expression (\x xs -> (f x):xs), as suggested by "Aadit M Shah"...
(:) is equal to (\x xs -> x:xs), because : is an operator and its function is (:)
. can be used to combine the function f with (:), hence (\x xs -> (f x):xs) is equal to ((:) . f)
main :: IO ()
main = print $ my_map (^(3 :: Int)) ([] :: [Integer])
my_map :: (a -> b) -> [a] -> [b]
my_map f xx = foldr ((:) . f) [] xx
Currying
A function of the form
-- v v
f a b c = .... c
can be reduced to
-- v v
f a b = ....
and a function of the form
-- v v v v
f a b c = .... b c
can be reduced to
-- v v v v
f a = ....
and so on, by currying.
Hence, my_map f xx = foldr ((:) . f) [] xx equals my_map f = foldr ((:) . f) [].
Combination and flip
flip flips the first two parameters.
Example, the following functions are equal:
f' a b c = (\c' b' a' -> ((a' - b') / c')) b a c
f'' a b c = flip (\c' b' a' -> ((a' - b') / c')) a b c
f''' = flip (\c' b' a' -> ((a' - b') / c'))
Hence, the following code works as well.
main :: IO ()
main = print $ my_map (^(3 :: Int)) ([1..5] :: [Integer])
my_map :: (a -> b) -> [a] -> [b]
my_map f = flip foldr [] ((:) . f)
But we can not get rid of f as above, because of the form in the expression flip foldr [] ((:) . f).
If we remove f ...
`((:) . f)` has type `a -> [a] -> [a]
-- v
`((:) . )` has type `(a -> a) -> a -> [a] -> [a]`
and
`flip foldr []` has type `Foldable t => (a1 -> [a2] -> [a2]) -> t a1 -> [a2]`
hence
f :: a -> a
is passed to
((:) . )
becomming
a -> [a] -> [a]
is passed to
flip foldr []
becomming
t a1 -> [a2]
Hence,
main :: IO ()
main = print $ my_map (^(3 :: Int)) ([1..5] :: [Integer])
my_map :: (a -> b) -> [a] -> [b]
my_map = flip foldr [] . ((:) . )
works nicely.

Related

apply a function n times to the n-th item in a list in haskell

I want a higher-order function, g, that will apply another function, f, to a list of integers such that
g = [f x1, f(f x2), f(f(f x3)), … , f^n(xn)]
I know I can map a function like
g :: (Int -> Int) -> [Int] -> [Int]
g f xs = map f xs
and I could also apply a function n-times like
g f xs = [iterate f x !! n | x <- xs]
where n the number of times to apply the function. I know I need to use recursion, so I don't think either of these options will be useful.
Expected output:
g (+1) [1,2,3,4,5] = [2,4,6,8,10]
You can work with explicit recursion where you pass each time the function to apply and the tail of the list, so:
g :: (Int -> Int) -> [Int] -> [Int]
g f = go f
where go _ [] = []
go fi (x:xs) = … : go (f . fi) xs
I here leave implementing the … part as an exercise.
Another option is to work with two lists, a list of functions and a list of values. In that case the list of functions is iterate (f .) f: an infinite list of functions that can be applied. Then we can implement g as:
g :: (Int -> Int) -> [Int] -> [Int]
g f = zipWith ($) (iterate (f .) f)
Sounds like another use for foldr:
applyAsDeep :: (a -> a) -> [a] -> [a]
applyAsDeep f = foldr (\x xs -> f x : map f xs) []
λ> applyAsDeep (+10) [1,2,3,4,5]
[11,22,33,44,55]
If you want to go a bit overkill ...
import GHC.Exts (build)
g :: (a -> a) -> [a] -> [a]
g f xs0 =
build $ \c n ->
let go x r fi = fi x `c` r (f . fi)
in foldr go (const n) xs0 f

How can I map a function to a list and stop when a condition is fulfilled and tell me if it stopped or reached the end?

I want to apply a function over a list, but if, at any moment, a result returned by the function is of a certain kind, then I don't want to continue to iterate over the rest of the elements.
I know I could achieve this with this function:
example p f ls = takeWhile p $ map f ls
The thing is that I would like to know if it reached the end of the list, or if it failed to do so.
I thought of this function, but it seems a bit cumbersome:
haltmap :: Eq a => (a -> Bool) -> (b -> a) -> [a] -> [b] -> Either [a] [a]
haltmap _ _ acc [] = Right acc
haltmap p f acc (h:t)
| p output = Left acc
| otherwise = haltmap p f (acc ++ [output]) t
where output = f h
I use Left and Right to know if it went through the entire list or not.
I'm sure there's a better way to do that.
I'd use span for this. It's like takeWhile but it gives you a pair with the remainder of the list as well as the matching part, like this:
> span (<3) [1,2,3,2,1]
([1,2],[3,2,1])
Then you can check if the remainder is empty:
haltmap :: (a -> Bool) -> (b -> a) -> [b] -> Either [a] [a]
haltmap p f xs = (if null rest then Right else Left) ys
where
(ys, rest) = span p (map f xs)
You can use foldr for this. Because go does not evaluate the second argument unless needed, this will also work for infinite lists. (Will Ness also had an answer that also used foldr, but it seems they've deleted it).
import Data.Bifunctor (bimap)
haltmap :: Eq a => (b -> Bool) -> (a -> b) -> [a] -> Either [b] [b]
haltmap p f xs = foldr go (Right []) xs
where
go x a
| p output = let o = (output:) in bimap o o a
| otherwise = Left []
where output = f x
main = do
print $ haltmap (<5) (+1) [1..]
print $ haltmap (<12) (+1) [1..10]
Try it online!
Using a tuple with a Bool may be easier, though.
import Data.Bifunctor (second)
haltmap :: Eq a => (b -> Bool) -> (a -> b) -> [a] -> (Bool, [b])
haltmap p f xs = foldr go (True, []) xs
where
go x a
| p output = second (output:) a
| otherwise = (False, [])
where output = f x
haltmap (<5) (+1) [1..] //(False,[2,3,4])
haltmap (<12) (+1) [1..10] //(True,[2,3,4,5,6,7,8,9,10,11])
Try it online!
I found a solution with foldr, which is the following:
haltMap :: (a -> Bool) -> (b -> a) -> [b] -> Either [a] [a]
haltMap p f = foldr (\x acc -> if p x then Left []
else (either (\a -> Left (x:a)) (\b -> Right (x:b)) acc))
(Right []) . map f
Also, to return, instead of the partial list, the element which failed, all is needed it to change Left [] to Left x in the if clause, and change the (\a -> Left (x:a)) to Left in the else clause.

Lambdas and Folds (Left and Right)

I really don't understand code
myReverse'' :: [a] -> [a]
myReverse'' xs = foldr (\x fId empty -> fId (x : empty)) id xs []
In case:
empty mapping to [] <---- accumulator
id mapping to fID (func id)
x is first element of xs (list)
Can i sort/change the postion of agruments "id xs []" ?
myReverse'' xs = foldr (\x fId empty -> fId (x : empty)) xs id []
I have read a book yesterday http://learnyouahaskell.com/higher-order-functions#lambdas
elem' :: (Eq a) => a -> [a] -> Bool
elem' y ys = foldl (\acc x -> if x == y then True else acc) False ys
The explanation is understandable to me.
the left fold's binary function has the accumulator as the first parameter and the current value as the second one (so \acc x -> ...)
or I can write as
elem' :: (Eq a) => a -> [a] -> Bool
elem' y ys = foldr (\x acc -> if x == y then True else acc) False ys
Anyone, can help/guide/explain me ?
Many thanks!
The way I like to understand these "reverse list with foldr" problems is to split it into pieces, and apply the lesson of "Foldr is made of monoids". Don't worry, this isn't as scary as it sounds.
First, let's note that reverse can be implemented this way:
my_reverse xs = foldl (flip (:)) xs []
This is the first simplification to our problem: if we can figure out how to write foldl in terms of foldr, then we can plug that solution into my_reverse to and be done with it.
Now, the standard type signature for foldr is this:
foldr :: (a -> r -> r) -> r -> [a] -> r
But the order of the arguments doesn't really matter, so let's rearrange things this way (throwing in a few implicit parentheses as well), and we'll compare it with map:
my_foldr :: (a -> (r -> r)) -> [a] -> (r -> r)
map :: (a -> b ) -> [a] -> [b]
Once you see this correspondence, it's not hard to see that we can write my_foldr this way:
my_foldr :: (a -> (r -> r)) -> [a] -> (r -> r)
my_foldr f as = compose (map f as)
where compose :: [r -> r] -> (r -> r)
compose = foldr (.) id
Think of this in the following way:
The map operation is converting each element of the list into a "step" of the transformation that we apply to the r values.
The compose function takes the resulting list of "steps" and wires them all together, using the . operator.
And now the trick is that we can write a foldl counterpart with a small change:
my_foldl :: (a -> (r -> r)) -> [a] -> (r -> r)
my_foldl f as = compose (map f as)
where compose :: [r -> r] -> (r -> r)
compose = foldr (flip (.)) id
{- Example:
>>> my_foldl (:) [1..3] []
[3,2,1]
-}
All I did was change (.) to flip (.)! And note that my_foldl is written in terms of map and foldr... but map can be rewritten in terms of foldr as well:
my_map :: (a -> b) -> [a] -> [b]
my_map f = foldr (\a bs -> f a : bs) []
So we've ended up with a solution that's different and longer than the one you're trying to understand, but hopefully it's illuminating.
The crucial thing is how this work with difference lists. Let's write out some explicit conversions:
type DList a = [a]->[a]
emptyDList :: Dlist a
emptyDList = id
fromDList :: DList a -> [a]
fromDList f = f []
myReverse'' :: ∀ a . [a] -> [a]
myReverse'' xs = fromDList $ foldr revCons emptyDList xs
where revCons :: a -> DList a -> DList a
revCons x fId empty = fId $ x : empty
Note that revCons has three arguments, though its signature actually suggests only two: difference lists are really a function type, but you can think of these functions as an abstract optimised representation for concrete lists.
If you do:
Prelude :t \x fId empty -> fId (x : empty)
You will get:
\x fId empty -> fId (x : empty) :: a -> ([a] -> t) -> [a] -> t
This function type here is equivalent to:
a -> ([a] -> t) -> ([a] -> t)
which means a function (binary function) that takes two arguments (the second argument is a function i.e. [a] -> t) and returns a function (i.e. [a] -> t).
This binary function matches the first argument that foldr takes (i.e. a -> b -> b).
In other words, foldr (\x fId empty -> fId (x : empty)) takes two arguments: a function and a list and returns a function.
Prelude> :t foldr (\x fId empty -> fId (x : empty))
foldr (\x fId empty -> fId (x : empty))
:: ([a] -> t) -> [a] -> [a] -> t
Take this example: foldr (\x fId empty -> fId (x : empty)) id [1, 2, 3].
Step 1: 3 and id are passed to the anonymous binary function as arguments. A function like \empty -> id (3 : empty) is returned as the new accumulator value.
Step 2: 2 and \empty -> id (3 : empty) are passed to the anonymous binary function. And \empty -> id (3 : (2 : empty)) is returned.
Step 3: 1 and \empty -> id (3 : (2 : empty)) are passed to the anonymous binary function. And \empty -> id (3 : (2 : (1 : empty))) is returned.
So foldr (\x fId empty -> fId (x : empty)) id [1, 2, 3] produces a function like \empty -> id (3 : (2 : (1 : empty))).
If you apply \empty -> id (3 : (2 : (1 : empty))) to [], then it will give you [3, 2, 1].
This means foldr (\x fId empty -> fId (x : empty)) id [1, 2, 3] [] produces [3, 2, 1].

Why can you reverse list with foldl, but not with foldr in Haskell

Why can you reverse a list with the foldl?
reverse' :: [a] -> [a]
reverse' xs = foldl (\acc x-> x : acc) [] xs
But this one gives me a compile error.
reverse' :: [a] -> [a]
reverse' xs = foldr (\acc x-> x : acc) [] xs
Error
Couldn't match expected type `a' with actual type `[a]'
`a' is a rigid type variable bound by
the type signature for reverse' :: [a] -> [a] at foldl.hs:33:13
Relevant bindings include
x :: [a] (bound at foldl.hs:34:27)
acc :: [a] (bound at foldl.hs:34:23)
xs :: [a] (bound at foldl.hs:34:10)
reverse' :: [a] -> [a] (bound at foldl.hs:34:1)
In the first argument of `(:)', namely `x'
In the expression: x : acc
Every foldl is a foldr.
Let's remember the definitions.
foldr :: (a -> s -> s) -> s -> [a] -> s
foldr f s [] = s
foldr f s (a : as) = f a (foldr f s as)
That's the standard issue one-step iterator for lists. I used to get my students to bang on the tables and chant "What do you do with the empty list? What do you do with a : as"? And that's how you figure out what s and f are, respectively.
If you think about what's happening, you see that foldr effectively computes a big composition of f a functions, then applies that composition to s.
foldr f s [1, 2, 3]
= f 1 . f 2 . f 3 . id $ s
Now, let's check out foldl
foldl :: (t -> a -> t) -> t -> [a] -> t
foldl g t [] = t
foldl g t (a : as) = foldl g (g t a) as
That's also a one-step iteration over a list, but with an accumulator which changes as we go. Let's move it last, so that everything to the left of the list argument stays the same.
flip . foldl :: (t -> a -> t) -> [a] -> t -> t
flip (foldl g) [] t = t
flip (foldl g) (a : as) t = flip (foldl g) as (g t a)
Now we can see the one-step iteration if we move the = one place leftward.
flip . foldl :: (t -> a -> t) -> [a] -> t -> t
flip (foldl g) [] = \ t -> t
flip (foldl g) (a : as) = \ t -> flip (foldl g) as (g t a)
In each case, we compute what we would do if we knew the accumulator, abstracted with \ t ->. For [], we would return t. For a : as, we would process the tail with g t a as the accumulator.
But now we can transform flip (foldl g) into a foldr. Abstract out the recursive call.
flip . foldl :: (t -> a -> t) -> [a] -> t -> t
flip (foldl g) [] = \ t -> t
flip (foldl g) (a : as) = \ t -> s (g t a)
where s = flip (foldl g) as
And now we're good to turn it into a foldr where type s is instantiated with t -> t.
flip . foldl :: (t -> a -> t) -> [a] -> t -> t
flip (foldl g) = foldr (\ a s -> \ t -> s (g t a)) (\ t -> t)
So s says "what as would do with the accumulator" and we give back \ t -> s (g t a) which is "what a : as does with the accumulator". Flip back.
foldl :: (t -> a -> t) -> t -> [a] -> t
foldl g = flip (foldr (\ a s -> \ t -> s (g t a)) (\ t -> t))
Eta-expand.
foldl :: (t -> a -> t) -> t -> [a] -> t
foldl g t as = flip (foldr (\ a s -> \ t -> s (g t a)) (\ t -> t)) t as
Reduce the flip.
foldl :: (t -> a -> t) -> t -> [a] -> t
foldl g t as = foldr (\ a s -> \ t -> s (g t a)) (\ t -> t) as t
So we compute "what we'd do if we knew the accumulator", and then we feed it the initial accumulator.
It's moderately instructive to golf that down a little. We can get rid of \ t ->.
foldl :: (t -> a -> t) -> t -> [a] -> t
foldl g t as = foldr (\ a s -> s . (`g` a)) id as t
Now let me reverse that composition using >>> from Control.Arrow.
foldl :: (t -> a -> t) -> t -> [a] -> t
foldl g t as = foldr (\ a s -> (`g` a) >>> s) id as t
That is, foldl computes a big reverse composition. So, for example, given [1,2,3], we get
foldr (\ a s -> (`g` a) >>> s) id [1,2,3] t
= ((`g` 1) >>> (`g` 2) >>> (`g` 3) >>> id) t
where the "pipeline" feeds its argument in from the left, so we get
((`g` 1) >>> (`g` 2) >>> (`g` 3) >>> id) t
= ((`g` 2) >>> (`g` 3) >>> id) (g t 1)
= ((`g` 3) >>> id) (g (g t 1) 2)
= id (g (g (g t 1) 2) 3)
= g (g (g t 1) 2) 3
and if you take g = flip (:) and t = [] you get
flip (:) (flip (:) (flip (:) [] 1) 2) 3
= flip (:) (flip (:) (1 : []) 2) 3
= flip (:) (2 : 1 : []) 3
= 3 : 2 : 1 : []
= [3, 2, 1]
That is,
reverse as = foldr (\ a s -> (a :) >>> s) id as []
by instantiating the general transformation of foldl to foldr.
For mathochists only. Do cabal install newtype and import Data.Monoid, Data.Foldable and Control.Newtype. Add the tragically missing instance:
instance Newtype (Dual o) o where
pack = Dual
unpack = getDual
Observe that, on the one hand, we can implement foldMap by foldr
foldMap :: Monoid x => (a -> x) -> [a] -> x
foldMap f = foldr (mappend . f) mempty
but also vice versa
foldr :: (a -> b -> b) -> b -> [a] -> b
foldr f = flip (ala' Endo foldMap f)
so that foldr accumulates in the monoid of composing endofunctions, but now to get foldl, we tell foldMap to work in the Dual monoid.
foldl :: (b -> a -> b) -> b -> [a] -> b
foldl g = flip (ala' Endo (ala' Dual foldMap) (flip g))
What is mappend for Dual (Endo b)? Modulo wrapping, it's exactly the reverse composition, >>>.
For a start, the type signatures don't line up:
foldl :: (o -> i -> o) -> o -> [i] -> o
foldr :: (i -> o -> o) -> o -> [i] -> o
So if you swap your argument names:
reverse' xs = foldr (\ x acc -> x : acc) [] xs
Now it compiles. It won't work, but it compiles now.
The thing is, foldl, works from left to right (i.e., backwards), whereas foldr works right to left (i.e., forwards). And that's kind of why foldl lets you reverse a list; it hands you stuff in reverse order.
Having said all that, you can do
reverse' xs = foldr (\ x acc -> acc ++ [x]) [] xs
It'll be really slow, however. (Quadratic complexity rather than linear complexity.)
You can use foldr to reverse a list efficiently (well, most of the time in GHC 7.9—it relies on some compiler optimizations), but it's a little weird:
reverse xs = foldr (\x k -> \acc -> k (x:acc)) id xs []
I wrote an explanation of how this works on the Haskell Wiki.
foldr basically deconstructs a list, in the canonical way: foldr f initial is the same as a function with patterns:(this is basically the definition of foldr)
ff [] = initial
ff (x:xs) = f x $ ff xs
i.e. it un-conses the elements one by one and feeds them to f. Well, if all f does is cons them back again, then you get the list you originally had! (Another way to say that: foldr (:) [] ≡ id.
foldl "deconstructs" the list in inverse order, so if you cons back the elements you get the reverse list. To achieve the same result with foldr, you need to append to the "wrong" end – either as MathematicalOrchid showed, inefficiently with ++, or by using a difference list:
reverse'' :: [a] -> [a]
reverse'' l = dl2list $ foldr (\x accDL -> accDL ++. (x:)) empty l
type DList a = [a]->[a]
(++.) :: DList a -> DList a -> DList a
(++.) = (.)
emptyDL :: DList a
emptyDL = id
dl2list :: DLList a -> [a]
dl2list = ($[])
Which can be compactly written as
reverse''' l = foldr (flip(.) . (:)) id l []
This is what foldl op acc does with a list with, say, 6 elements:
(((((acc `op` x1) `op` x2) `op` x3) `op` x4) `op` x5 ) `op` x6
while foldr op acc does this:
x1 `op` (x2 `op` (x3 `op` (x4 `op` (x5 `op` (x6 `op` acc)))))
When you look at this, it becomes clear that if you want foldl to reverse the list, op should be a "stick the right operand to the beginning of the left operand" operator. Which is just (:) with arguments reversed, i.e.
reverse' = foldl (flip (:)) []
(this is the same as your version but using built-in functions).
When you want foldr to reverse the list, you need a "stick the left operand to the end of the right operand" operator. I don't know of a built-in function that does that; if you want you can write it as flip (++) . return.
reverse'' = foldr (flip (++) . return) []
or if you prefer to write it yourself
reverse'' = foldr (\x acc -> acc ++ [x]) []
This would be slow though.
A slight but significant generalization of several of these answers is that you can implement foldl with foldr, which I think is a clearer way of explaining what's going on in them:
myMap :: (a -> b) -> [a] -> [b]
myMap f = foldr step []
where step a bs = f a : bs
-- To fold from the left, we:
--
-- 1. Map each list element to an *endomorphism* (a function from one
-- type to itself; in this case, the type is `b`);
--
-- 2. Take the "flipped" (left-to-right) composition of these
-- functions;
--
-- 3. Apply the resulting function to the `z` argument.
--
myfoldl :: (b -> a -> b) -> b -> [a] -> b
myfoldl f z as = foldr (flip (.)) id (toEndos f as) z
where
toEndos :: (b -> a -> b) -> [a] -> [b -> b]
toEndos f = myMap (flip f)
myReverse :: [a] -> [a]
myReverse = myfoldl (flip (:)) []
For more explanation of the ideas here, I'd recommend reading Tom Ellis' "What is foldr made of?" and Brent Yorgey's "foldr is made of monoids".

Define map using foldl instead of foldr and an expr

I did it like this – but it is not working:
ma f [] = []
ma f (xs) = foldl (\y ys -> ys++(f y)) [] xs
foldl :: (a -> b -> a) -> a -> [b] -> a
foldr :: (a -> b -> b) -> b -> [a] -> b
Why is there a difference in the function that fold takes. I mean, (a -> b -> a) and (a -> b -> b)?
Is it possible to define map using foldl?
I have another question
I have an expr.
map (:)
I want to know what it will do. I tried to test it but i only get error.
type is map (:) :: [a] -> [[a] -> [a]]
I tried to send in a list of [1,2,3]
Not if you want it to work for infinite as well as finite lists. head $ map id (cycle [1]) must return 1.
foldling over an infinite list diverges (never stops), because foldl is recursive. For example,
foldl g z [a,b,c] = g (g (g z a) b) c
Before g gets a chance to ignore its argument, foldl must reach the last element of the input list, to construct the first call to g. There is no last element in an infinite list.
As for your new question, here's a GHCi transcript that shows that map (:) is a function, and map (:) [1,2,3] is a list of functions, and GHCi just doesn't know how to Show functions:
Prelude> map (:)
<interactive>:1:0:
No instance for (Show ([a] -> [[a] -> [a]]))
Prelude> :t map (:)
map (:) :: [a] -> [[a] -> [a]]
Prelude> map (:) [1,2,3]
<interactive>:1:0:
No instance for (Show ([a] -> [a]))
Prelude> :t map (:) [1,2,3]
map (:) [1,2,3] :: (Num a) => [[a] -> [a]]
Prelude> map ($ [4]) $ map (:) [1,2,3]
[[1,4],[2,4],[3,4]]
Prelude> foldr ($) [4] $ map (:) [1,2,3]
[1,2,3,4]
It becomes more obvious when you swap the type-variable names in one of the functions:
foldl :: (b -> a -> b) -> b -> [a] -> b
foldr :: (a -> b -> b) -> b -> [a] -> b
...because after all, what we need is the result, i.e. [a] -> b. Or, more specially, [a] -> [b], so we might as well substitute that
foldl :: ([b] -> a -> [b]) -> [b] -> [a] -> [b]
foldr :: (a -> [b] -> [b]) -> [b] -> [a] -> [b]
which leaves only one non-list item in each signature, namely the a. That's what we can apply f to, so, in the case of foldl it has to be the 2nd argument of the lambda:
foldl (\ys y -> ys ++ f y)
As Xeo remarks, this isn't done yet, because f y has type b, not [b]. I think you can figure out how to fix that yourself...
ma f [] = []
ma f (xs) = foldl (\ys y -> ys++[(f y)]) [] xs
Works but why does order of arg to lambda matter.
ma f (xs) = foldl (\y ys -> ys++[(f y)]) [] xs gives error

Resources